Binary hole transport materials blending to linearly tune HOMO level for high efficiency and stable perovskite solar cells. (September 2018) - Yin, Xinxing; Wang, Changlei; Zhao, Dewei; Shrestha, Niraj; Grice, Corey R.; Guan, Lei; Song, Zhaoning; Chen, Cong; Li, Chongwen; Chi, Guoli; Zhou, Baojing; Yu, Jiangsheng; et al.
Abstract: To maximize the photovoltaic performance of perovskite solar cells (PVSCs）by developing new hole-transport layer (HTL) materials, the precise tuning of their energy levels especially the highest occupied molecular orbital (HOMO) is highly desirable. Here, a simple binary strategy for the first time is proposed to acquire ideal HOMO level by optimizing the composition of binary blend HTLs including CZ-TA (HOMO = −5.170 eV) and CZ-STA (HOMO = −5.333 eV). By adding 10 wt% CZ-STA, the binary HTM (HOMO = −5.199 eV) based perovskite solar cells achieve a maximum power conversion efficiency of 19.85% (18.32% for CZ-TA). The introducing of S atom in CZ-STA not only downshifts HOMO level but also forms stronger Pb-S interaction with perovskites than Pb-O in CZ-TA, leading to better device performance and reduced hysteresis. Importantly, the un-encapsulated PVSCs using CZ-TA:CZ-STA (90:10, w/w) binary HTL exhibit good environment stability in ambient air, maintaining over 82% of their initial efficiency after 60 days' storage with a relative humidity around 50%. Therefore, this strategy provides new insights on HTL development to push forward the progress of the emerging PVSCs Graphical abstract: Binary hole transport materials blending to linearly tuning HOMO level for high efficiency and stable perovskite solar cells have been developed for the first time. Ideal HOMO level is acquired by optimizing the composition of binary HTLs. A maximum power conversion efficiency of 19.85% is achieved for cells with negligible hysteresis. The un-encapsulated devices maintain over 82% initial efficiency after 60 days' storage with ~ 50% relative humidity. fx1 Highlights: Binary alloying of two hole transport materials (HTMs) to linearly tune HOMO level of HTL. Development of S-terminating HTM to form stronger Pb-S interaction in perovskites. Binary HTL leading to a maximum power conversion efficiency of 19.85% for perovskite solar cells. Better device performance and reduced hysteresis for the devices. 82% efficiency retention after 60 days' storage with a relative humidity ~ 50%.